Acting out when psychosocial safety climate is low: understanding why middle-level managers experience upward mistreatment - Loh, May Young; Dollard, Maureen Frances (Frontiers in Psychology, 2024)
Introduction Upward mistreatment, despite being under studied, is an influential phenomenon affecting middle managers’ well-being and performance. The work environment hypothesis of bullying proposes that an undesirable work context is the main cause of workplace bullying, suggesting the importance of creating an anti-mistreatment climate, that is, psychosocial safety climate (PSC). In this study, we argue that upward bullying and aggression are unsafe behaviors, a “retaliation” by employees resulting from their unsafe work context. Methods Using a large-scale multisource sample collected from 123 organizations, 6,658 middle managers and 34,953 employees, we examined the relationship between collective PSC, individual-perceived PSC and middle managers’ experience of upward mistreatment. Results Single-level and multi-level modeling results suggested that PSC is an important element in reducing the likelihood of upward bullying and aggression, in turn, protecting managers’ well-being. More importantly, upward bullying is a way that employees act out when there is an undesirable working context. Discussion Future research on workplace mistreatment should examine PSC and upward mistreatment. Interventions provided should focus on improving PSC which could in turn preventing upward mistreatment, thereby improving psychosocial safety for both employees and middle managers to prevent negative actions.